On the Role of Individual Learner Differences in the Teaching / Learning of Foreign Languages: The Dimension of Field Dependence / Field Independence. With Morals for EFL Teaching - Jantarska, Anna (Respectus Philologicus, 2006)
The aim of this article is to present and discuss the results of a correlational study, the subject matter of which is the relationship between the cognitive style of field dependence/field independence and reading comprehension. The paper attempts to stress the role of individual learner differences in the process of second language acquisition. Therefore, the emphasis is placed on applying psychological issues to the educational context. The reader is presented with empirical research results and an in-depth analysis of these findings, followed by implications for the EFL classroom.
Keywords: cognitive style; field dependence; field independence; reading comprehension; second language acquisition; individual learner differences